Obraz kobiety włoskiej w literaturze XIX wieku i jego realizacja w Półdiablęciu weneckim Józefa Ignacego Kraszewskiego - Bartnikowska-Biernat, Magdalena (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The type of la donna Italiana, the statuesque woman with dark hair, light skin and large, black, hypnotic eyes was popularized among the European men of letters in the nineteenth century. This stereotype had already been solidified in eighteenth-century Italian phraseology, but it was later brought into general use by Madame de Staël and George Byron. The Italian poet of the late nineteenth century, Annetta Ceccoli Boneschi, gathered and described the most distinctive features of the female citizens of different regions of Italy used by foreign writers to create their heroines. Among others, the Venetians were supposed to be the most beautiful and seductive women, with their soft accent and smouldering gaze. In Poland, this type of heroine appeared in Józef Ignacy Kraszewski’s novel The Half-Demon of Venice, which is the main focus of this article. The creation of an Italian donna in this romance uses the stereotypes formed during the nineteenth century, but it also uses the individual observations made by Kraszewski himself during his tour through Italy.